TINJAUAN HUKUM TERHADAP PERBUATAN MENGHALANGI OJEK ONLINE YANG DILAKUKAN OLEH BECAK MOTOR DI PEKANBARU - Asri Indri Rahmadani; Firdaus Firdaus; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Unfair business competition is competition between business actors in carrying outproduction and or marketing activites of goods or services that are carried out in a dishonestor unlawful manner or impede business competition. Unfair business competition occursbetween online motorcycle taxis and motorized trishaws in the Tuah Karya sub-district.Where there is a ban between online motorcycle taxis and rickshaws which are prohibitedfrom taking passengers along the Suka karya road. Prohibit online motorcycle taxis frompicking up passengers if they are caught by motorized tricycles,online motorcycle taxis areobliged to drop off customers from the online motorbike taxis. The purposeof writing thisthesis:first to find out how the act of blocking online motorcycle taxis by motorized trishawsin Pekanbaru occurred. Second,what are the regulatory efforts that can be made so that theact of blocking motorcycle taxis from online motorcycle taxis does not occur in Pekanbaru.The approach to writing this research was carried out sociologically. Sociological,which means reviewing the state of the problems that exist in the field associated with thelegas aspects that apply and regulate these problems. This research was conducted in theTuah Madani sub-district, the Tuah Karya sub-district, namely at the crossroads of SukarKarya,Panam Pekanbaru. Sources of data used are primary data, secondary data andtertiary data with data colletion techniques by means of interviews,questionnaires andliterature review.From the results of research conducted it can be concluded. First, the motorizedrickshaws prevented online motorcycle taxis from picking up passengers in the Tuah Karyavillage because of several factors and the opinion of motorized rickshaws had decreased,many motorized rickshaws had become extinct due to online motorcycle taxis, so that's whymotorized rickshaws took action to block the online motorcycle taxis. Second, regarding fairbusiness competition, motorized rickshaws should be given more good guidance not to makepolicies unilaterally and to make special regulations regarding rights and obligations thatshould be.Keywords :Unfair Business Competition - Online Motorcycle taxis - Obstructive actions